Recovering unburned carbon from gasification fly ash using saline water. (October 2019) - Zhang, Rui; Guo, Fangyu; Xia, Yangchao; Tan, Jinlong; Xing, Yaowen; Gui, Xiahui
Highlights: Dosage of forther reduced effectively using saline water. Effect valence states of saline water on flotation was studied. Saline improves the stability of bubbles in flotation of gasification fly ash. Resource utilization of gasification fly ash can be realized. Abstract: Gasification fly ash is one of the wastes generated by coal gasifiers, and the unburned carbon therein seriously restricts the resource utilization of gasification fly ash. Flotation is one of the best ways to recover unburned carbon from it; however, surface pores of gasification fly ash are developed and contain several hollow hydrophilic glass beads, which makes it difficult for conventional flotation to recover unburned carbon effectively and the dosage of the flotation reagent is too high. In this study, different concentrations of saline water (NaCl, MgCl2, and AlCl3 ) are configured to the flotation solution, and their effect on the recovery of unburned carbon of gasification fly ash is investigated. Furthermore, the gasification fly ash treated with saline water is chosen to study the basic properties by the measurement of Zeta potential, surface tension, and flotation foam behavior. The experimental results show that with an increase in the valence state of the inorganic salt cation, the unburned carbon recovery efficiency of the gasification fly ash is significantly improved. When the concentration of Al 3+ reaches 0.4 mol/L and the dosage of frother is 7.5 kg/t, the unburned carbon removal rate of the tailings reaches 95% or more. Saline water reduces the surface tension of the flotation system and weakening bubble decay; in the solution of Al 3+, the flotation foam size is the smallest, followed by the solution of Mg 2+, Na + . Furthermore, the saline water effectively reduces the Zeta potential of the particle surface and improves the floatability of the solid particles.